Literature Review: Pengaruh Penerapan Model Problem-Based Learning (PBL) terhadap Keterampilan Kolaborasi Siswa - Arni Ramadhani; Marsella Evintaras Br Sebayang; Elsa Rima Prahesti; Huzaimah Huzaimah; Nevilia Pramesti Irawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Education today demands collaboration skills as one of the essential competencies to support the success of the learning process. However, students’ collaboration skills remain a challenge in classroom practice. One instructional model considered effective in enhancing students’ collaboration skills is Problem-Based Learning (PBL). This study aims to analyze the effect of implementing the Problem-Based Learning (PBL) model on students’ collaboration skills based on findings from previous studies.This study employs a literature review method with a systematic review approach guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Article searches were conducted using Publish or Perish through the Google Scholar database with relevant keywords. Articles were selected based on predefined inclusion and exclusion criteria and then screened through the stages of identification, screening, eligibility, and inclusion, resulting in 12 articles for further analysis.The results of the review indicate that the implementation of the Problem-Based Learning (PBL) model has a positive effect on improving students’ collaboration skills, particularly in terms of teamwork, communication, responsibility, and active participation in learning. These findings suggest that the PBL model is effective as an alternative instructional approach to support the development of students’ collaboration skills.